The great secret the classified World War II disaster that launched the war on cancer - Conant, Jennet (W. W. Norton & Company, 2020)
"The gripping story of a chemical weapons catastrophe, its cover-up, and how one army doctor's discovery led to the development of chemotherapy. On the night of December 2, 1943, the Luftwaffe bombed a critical Allied port in Bari, Italy, sinking seventeen ships and killing over a thousand servicemen and hundreds of civilians. Caught in the surprise air raid was the John Harvey, an American Liberty ship carrying a top-secret cargo of 2,000 mustard bombs to be used in retaliation if the Germans resorted to gas warfare. After young sailors began suddenly dying with mysterious symptoms, Lieutenant Colonel Stewart Alexander, a doctor and chemical weapons expert, was dispatched to investigate. He quickly diagnosed mustard gas exposure, which both Churchill and Eisenhower denied. But Alexander's breakthrough observations about the toxic effects of mustard on white blood cells, as well as the heroic perseverance of Colonel Cornelius P. Rhoads-a researcher and doctor as brilliant as he was arrogant and self-destructive- were instrumental in ushering in a new era of cancer research led by the Sloan Kettering Institute. The Great Secret is a remarkable story of how horrific tragedy gave birth to medical triumph."